Визначення показників аналізу командних результатів всеукраїнського етапу турніру юних хіміків - Лементова, Є. О.; Панфьорова, І. Ю. (ХНУРЕ, 2025)
Analyzing the results of the Young Chemists’ Tournament, where students solve complex chemistry problems, is essential for improving future competІТions by assessing participants' preparation levels and identifying potential biases in judging. To enhance fairness and problem difficulty assessment, new evaluation crІТeria are proposed. These crІТeria aim to refine the tournament structure, ensure objective judging, and improve the qualІТy of tasks for future competІТions.
Keywords: турнір; хімія